A Systematic Literature Review of Contextual Understanding and Digital Literacy of Elementary School Students through H5P-Based Learning Media - Setiyawan, Andhi Bagus (Social, Humanities, and Educational Studies (SHES): Conference Series, 2026)
The rapid development of digital technology in education demands the strengthening of 21st-century competencies, particularly contextual understanding and digital literacy among elementary school students. Contextual understanding enables students to relate learning concepts to real-life situations, while digital literacy supports their ability to access, evaluate, and utilize information effectively in a digital environment. However, previous studies indicate that these competencies have not been optimally developed, especially in learning abstract topics such as Exploring Earth and Space. Therefore, interactive, context-based learning media are needed to bridge this gap. One potential solution is the HTML5 Package (H5P), a web-based platform that enables the creation of interactive learning content and formative assessment tools. This study aims to analyze and synthesize research on students’ contextual understanding and digital literacy using H5P-based learning media. The method employed is a Systematic Literature Review (SLR) following the PRISMA procedure, which includes identification, screening, eligibility, and inclusion stages. Data were collected from the Google Scholar database, covering publications from 2020 to 2025 using the keywords “contextual understanding,” “digital literacy,” and “H5P.” Selected articles were filtered based on predetermined inclusion and exclusion criteria. The findings reveal that contextual learning approaches consistently improve students’ conceptual understanding by linking learning materials to real-life experiences. Meanwhile, students’ digital literacy levels vary, with a predominance in basic technical skills, while higher-order skills such as critical thinking and information evaluation remain underdeveloped. The integration of H5P has been shown to enhance student engagement, strengthen conceptual understanding, and foster digital literacy through interactive content and immediate feedback. Therefore, H5P-based learning media have strong potential as an innovative solution to integrate contextual understanding and digital literacy in elementary education.